(untitled) (CIPEEX, 2023)
The present work presents the ’State of the Art’ scheduled for the preparation of a Master’s Thesis being developed in the stricto sensu Graduate Program in Environmental Sciences at the Evangelical University of Goiás (UniEVANGÉLICA). The agenda highlights the importance of studies focused on Green Patents that serve the promotion and protection of the Environment in Brazil, serving as an effective tool for environmental sustainability. To achieve success, a deductive approach was employed, enhanced by bibliographic and documentary techniques, which allowed for the development of research of a descriptive and explanatory nature.